Understanding Online Repurchase Intention - Savitri, Citra; Rismayadi, Budi; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
The development of e-commerce provides opportunities for businesspeople to innovate and change in creating products according to the desires and needs of their consumers. This research was conducted to analyze the effect of brand equity, customer experience and repurchase intention on online stores for fashion products to the millennials. This research uses descriptive qualitative method with a sample size of 106 respondents with a range 24-30 years old. The results of the research prove that brand equity is in good criteria while customer experience and repurchase intention are in very good criteria. The influence between brand equity and customer experience is 9,105 while customer experience and repurchase intention are 0,263. The results of this research are expected to contribute to online companies to provide more value to the customer experience as a form of business strategy.